2003
DOI: 10.1175/1520-0450(2003)042<0505:mocspp>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Convective–Stratiform Precipitation Processes: Sensitivity to Partitioning Methods

Abstract: Six different convective-stratiform separation techniques, including a new technique that utilizes the ratio of vertical and terminal velocities, are compared and evaluated using two-dimensional numerical simulations of a tropical [Tropical Ocean Global Atmosphere Coupled Ocean-Atmosphere Response Experiment (TOGA COARE)] and midlatitude continental [Preliminary Regional Experiment for STORM-Central (PRESTORM)] squall line. Comparisons are made in terms of rainfall, cloud coverage, mass fluxes, apparent heatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
122
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(125 citation statements)
references
References 56 publications
3
122
0
Order By: Relevance
“…Additional information like cloud contents, vertical motion, and the fall speed of precipitation particles has been also used in partitioning methods (e.g. Tao et al, , 2000Sui et al, 1994;Xu, 1995;Lang et al, 2003). Lang et al (2003) conducted a comparison study using six different partitioning methods based on surface rain-rate, mass fluxes, apparent heating and moistening, hydrometeor contents, reflectivity and vertical velocity CFAD (Contoured Frequency with Altitude Diagram), microphysics, and latent heat retrieval (Churchill and House, 1984;Caniaux et al, 1994;Steiner et al, 1995;Xu, 1995;Lang et al, 2003), and showed that the method based on surface rain-rate was consistently the most stratiform whereas the method based on radar information below the melting level and the fall speed of precipitation particles was consistently the most convective.…”
Section: Discussionmentioning
confidence: 99%
“…Additional information like cloud contents, vertical motion, and the fall speed of precipitation particles has been also used in partitioning methods (e.g. Tao et al, , 2000Sui et al, 1994;Xu, 1995;Lang et al, 2003). Lang et al (2003) conducted a comparison study using six different partitioning methods based on surface rain-rate, mass fluxes, apparent heating and moistening, hydrometeor contents, reflectivity and vertical velocity CFAD (Contoured Frequency with Altitude Diagram), microphysics, and latent heat retrieval (Churchill and House, 1984;Caniaux et al, 1994;Steiner et al, 1995;Xu, 1995;Lang et al, 2003), and showed that the method based on surface rain-rate was consistently the most stratiform whereas the method based on radar information below the melting level and the fall speed of precipitation particles was consistently the most convective.…”
Section: Discussionmentioning
confidence: 99%
“…Convection-permitting models struggle to simultaneously capture convective and stratiform cloud processes, therefore modelobservational comparisons often emphasize bulk cloud regime segregations and contingent performances to diagnose issues with cloud model treatments (e.g., Lang et al, 2003). Although there is no clear line separating convective and stratiform processes (e.g., for identifying deficiencies in modeled precipitation, vertical air motions or heating profiles), bulk regime From a practical radar-based classification perspective that typically utilizes higher Z 40-45 dBZ thresholds, it follows that 25 standard methods may necessitate additional texture, peakedness or similar ideas to properly identify Amazon convection (e.g., Steiner et al, 1995).…”
Section: Amazon Precipitation Properties: Cumulative Dataset Charactementioning
confidence: 99%
“…The microphysical schemes used by NWP models often misrepresent the auto-conversion processes as well as the characteristics of cloud particles (e.g., size distribution, densities). The microphysical parameterization should be tuned to the different types of precipitation regimes (i.e., convective vs. stratiform) throughout the life cycle of the simulated event (Lang et al, 2003;Wu et al, 2013). Ground-based instruments such as weather radars and disdrometers can be used to gain insights about the microphysical structure of a precipitating cloud and to derive the parameters required by microphysics schemes.…”
Section: N Roberto Et Al: Multi-sensor Analysis Of Convective Activmentioning
confidence: 99%